Respuesta :
[tex]\bf \begin{cases} -7x+8y=1\\ 4x-8y=20 \end{cases}\qquad \qquad \stackrel{\textit{using elimination}}{ \begin{array}{llll} -7x~~\begin{matrix} +8y \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~=1\\ ~~4x~~\begin{matrix} -8y \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~=20\\ \cline{1-1}\\ -3x~\hfill =21 \end{array}}[/tex]
[tex]\bf x=\cfrac{21}{-3}\implies \blacktriangleright x=-7 \blacktriangleleft \\\\\\ \stackrel{\textit{substituting in the 2nd equation}}{4(-7)-8y=20}\implies -28-8y=20\implies -8y=48 \\\\\\ y=\cfrac{48}{-8}\implies \blacktriangleright y = -6 \blacktriangleleft[/tex]
Answer: -6
Step-by-step explanation:
First, try deleting the x-coordinate from the equations by making them the same number. By doing that I multiplied the first equation (-7x+8y=1) by 4 and (4x-8y=20) by 7. That got me -28x+32y=4 and +28x-56y=140. You could cross out the 28 which gets +32y=4 and -56y=140. Then add up both equations. It’s gets you -24y=144
-24y=144
—————— then divide by -24
-24 -24
144/-24=-6
Hope this helped!